Mass Media Gatekeepers for Colleges of Agriculture - J. Cordell Hatch (Journal of Applied Communications, 1971)
To reach the public, most news and information from colleges of agriculture must pass through an intermediary. This man in the middle is called a "mass media gatekeeper." He literally has the power to open or close the gate to any material he gets from colleges of agriculture.